Evaluación de la eficiencia en los Procesos de la Gestión Administrativa del Distrito De Educación 13D12 Rocafuerte – Tosagua, período 2022 - Cedeño Quiroz, Sara María (2024)
The objective of this research was to evaluate the efficiency of the Administrative Management processes of the 13D12 Rocafuerte – Tosagua Education District, in order to develop an improvement plan. A mixed-approach methodology was used, combining documentary and field research. The research was carried out in three stages: first, the processes were characterized through a documentary review, a semi-structured interview with the director of the institution and the preparation of process sheets; in the second phase, the efficiency of the processes was measured using the AVA matrix, analyzing the time allocated to the activities; finally, a proposal for improvement was developed through a planning matrix that specified lines of action for the deficient processes, specifically for the activities that do not add value. The findings allowed us to determine that three of the five processes studied are inefficient, due to the significant time spent on carrying out preparation, inspection and waiting activities. It is concluded that the administrative management of the institution requires important improvements to maximize the efficiency of its processes and subprocesses, and thus generate greater added value in its operations for the satisfaction of its users.